Comparison of Pudendal Nerve Blockade, Tenoxicam Suppository and Rectal Lidocaine Gel Anesthesia for Transrectal Ultrasound-Guided Biopsy of the Prostate (Annals of Medical Research, 2021)
Aim: We assessed the safety and efficacy of three different local anesthesia methods (pudendal nerve blockade, tenoxicam suppository and rectal lidocaine gel) before transrectal ultrasound (TRUS)-guided biopsy of the prostate in this study.
Keywords: Prostate Biopsy, Anesthesia, Pain, Pudendal Nerve Blockade, Tenoxicam Suppository